Calcium/Calmodulin-Dependent Protein Kinase II Activity Persists During Chronic β-Adrenoceptor Blockade in Experimental and Human Heart Failure. (May 2017) - Dewenter, Matthias; Neef, Stefan; Vettel, Christiane; Lämmle, Simon; Beushausen, Christina; Zelarayan, Laura C.; Katz, Sylvia; von der Lieth, Albert; Meyer-Roxlau, Stefanie; Weber, Silvio; Wieland, Thomas; Sossalla, Samuel; et al.
Abstract : Background—: Considerable evidence suggests that calcium/calmodulin-dependent protein kinase II (CaMKII) overactivity plays a crucial role in the pathophysiology of heart failure (HF), a condition characterized by excessive β-adrenoceptor (β-AR) stimulation. Recent studies indicate a significant cross talk between β-AR signaling and CaMKII activation presenting CaMKII as a possible downstream mediator of detrimental β-AR signaling in HF. In this study, we investigated the effect of chronic β-AR blocker treatment on CaMKII activity in human and experimental HF. Methods and Results—: Immunoblot analysis of myocardium from end-stage HF patients (n=12) and non-HF subjects undergoing cardiac surgery (n=12) treated with β-AR blockers revealed no difference in CaMKII activity when compared with non–β-AR blocker–treated patients. CaMKII activity was judged by analysis of CaMKII expression, autophosphorylation, and oxidation and by investigating the phosphorylation status of CaMKII downstream targets. To further evaluate these findings, CaMKIIδC transgenic mice were treated with the β1 -AR blocker metoprolol (270 mg/kg*d). Metoprolol significantly reduced transgene-associated mortality (n≥29; P <0.001), attenuated the development of cardiac hypertrophy (−14±6% heart weight/tibia length; P <0.05), and strongly reduced ventricular arrhythmias (−70±22% premature ventricular contractions; P <0.05). On a molecular level, metoprolol expectedly decreased protein kinase A–dependent phospholamban and ryanodine receptor 2 phosphorylation (−42±9% for P-phospholamban-S16 and −22±7% for P-ryanodine receptor 2-S2808; P <0.05). However, this was paralled neither by a reduction in CaMKII autophosphorylation, oxidation, and substrate binding nor a change in the phosphorylation of CaMKII downstream target proteins (n≥11). The lack of CaMKII modulation by β-AR blocker treatment was confirmed in healthy wild-type mice receiving metoprolol. Conclusions—: Chronic β-AR blocker therapy in patients and in a mouse model of CaMKII-induced HF is not associated with a change in CaMKII activity. Thus, our data suggest that the molecular effects of β-AR blockers are not based on a modulation of CaMKII. Directly targeting CaMKII may, therefore, further improve HF therapy in addition to β-AR blockade. Abstract : Supplemental Digital Content is available in the text.